Nonverbal communication means in the UK parliamentary debates - Pietsukh, Oksana (Տիգրան Մեծ)
This article focuses on the proxemics, oculesics and tacesics as nonverbal communication pecu-liarities in the UK parliamentary debates within the scope of parliamentary discourse studies (discour-sology)as a new branch of political discourse studies. It deals with studies ofmetonymy-based language representations of space used to name the MPs in the UK parliamentary debates. Here, the visual charac-teristics and behavioral patterns influencing MPs‟ role and participationin the debates are highlighted.The paper determines cognitive background and extralinguistic factors influencing the usage of naming models and MPs‟ colour determinationin parliamentary debates. Such debates represent the events regardless of the party that gains the majority in the UK parliament in post-Thatcher period. It is concluded that nonver-balcommunicationhasbecome an inseparable part of parliamentary communication, serving as a uniquecommunicative code used by the MPs. The results stipulate further modelling of the parliamentary debates to build their interactive and cognitive models for better insight into the British political life and the British national character. The received knowledge is of particular importance for teaching country studies, histo-ry of the UK, political science, and speech communication theory.
Keywords: Philosophy